Clinical and demographic characteristics related to onset site and spread of cervical dystonia. Issue 12 (18th October 2016) - Norris, Scott A.; Jinnah, H. A.; Espay, Alberto J.; Klein, Christine; Brüggemann, Norbert; Barbano, Richard L.; Malaty, Irene Andonia C.; Rodriguez, Ramon L.; Vidailhet, Marie; Roze, Emmanuel; Reich, Stephen G.; Berman, Brian D.; et al.
ABSTRACT: Background: Clinical characteristics of isolated idiopathic cervical dystonia such as onset site and spread to and from additional body regions have been addressed in single‐site studies with limited data and incomplete or variable dissociation of focal and segmental subtypes. The objectives of this study were to characterize the clinical characteristics and demographics of isolated idiopathic cervical dystonia in the largest standardized multicenter cohort. Methods: The Dystonia Coalition, through a consortium of 37 recruiting sites in North America, Europe, and Australia, recruited 1477 participants with focal (60.7%) or segmental (39.3%) cervical dystonia on examination. Clinical and demographic characteristics were evaluated in terms of the body region of dystonia onset and spread. Results: Site of dystonia onset was: (1) focal neck only (78.5%), (2) focal onset elsewhere with later segmental spread to neck (13.3%), and (3) segmental onset with initial neck involvement (8.2%). Frequency of spread from focal cervical to segmental dystonia (22.8%) was consistent with prior reports, but frequency of segmental onset with initial neck involvement was substantially higher than the 3% previously reported. Cervical dystonia with focal neck onset, more than other subtypes, was associated with spread and tremor of any type. Sensory tricks were less frequent in cervical dystonia with segmental components, and segmental cervical onset occurred at an older age. Conclusions: Subgroups had modest but significant differences in the clinical characteristics that may represent different clinical entities or pathophysiologic subtypes. These findings are critical for design and implementation of studies to describe, treat, or modify disease progression in idiopathic isolated cervical dystonia. © 2016 International Parkinson and Movement Disorder Society.